The Hybrid Approach for Sentimental Analysis of Twitter Data - Kajal; Verma, Prince (International Journal of Computer Sciences and Engineering, 2019)
Any kind of attitude, through or judgment that occurs due to any feeling is known as a sentiment which is also known as opinion mining. The sentiments of individuals towards particular elements are analyzed in this approach. To gather sentiment information, web or internet is the best known source. A platform that is accessed socially by various users to post their views is known as Twitter. The messages that are posted by these users are known as tweets. The properties of Tweets are highly unique due to which new challenges have raised. In comparison to several other domains, the sentiment analysis requires higher analysis studies. This research work is based on the sentiment analysis of product reviews of Amazon data. To apply sentiment analysis the technique of feature extraction and classification is applied. For the sentiment analysis in the previous work, the SVM technique is applied and which is replaced with the KNN technique.